Le rite (a)religieux dans La chaise au fond de l’œil d’Aude - Kapołka, Karolina (Romanica Silesiana)
The novel by Aude (Claudette Charbonneau‑Tissot), a Quebec writer, spotlights a woman who is swept into the shackles of madness which she then consciously leaves behind only to commit suicide. Her rejection of the inertia and the roles imposed on her raises the fundamental questions about life and death, conscience and freedom. The difficulty with living a life becomes a philosophical problem, superficially devoid of a religious dimension as the protagonist is an atheist. The novel can thereby be read as a possible illustration of the secularization of Quebec, whose culture once deeply marked with Catholic traits is now showing its religionless face. At the same time, the sacred continues to be a crucial factor in that it passes its message in the language interspersed with Biblical images and liturgical rituals. The opposition between the rationalist view which underlies the protagonist’s decisions and the Catholic heritage which spills unconsciously into her thoughts is the focal point of this study. Key words: ritual, death, religion, Aude, Claudette Charbonneau‑Tissot